Chronic heat stress and Salmonella enteritidis challenge in Japanese quail: Immune effects in adult and transgenerational consequences - Giayetto, Octavio (2018)
Stressful events during production such as routine vaccination protocols and high environmental temperatures are common challenges for poultry species. Chicks? prenatal environment can be influenced by these events, inducing trans-generational effects. This study evaluated whether an immune challenge and a chronic heat stress (CHS) exposure on adult Japanese quail can modulate later immune responses and whether those effects can be reflected in their offspring. Eighty adults were inoculated with inactivated Salmonella enteritidis (challenge initiated at 115 d of age) and then exposed to a CHS along 9 d (between 121 to 129 d of age) by increasing the environmental temperatures from 25 to 34°C during the daylight hours. A 2 × 2 factorial experimental design was used and 4 treatments groups (20 birds each) were therefore defined: Non Challenged-Non Stressed, Challenged-Non Stressed, Non Challenged Stressed and Challenged-Stressed. Between 125 and 130 d of age, eggs were collected and incubated. Newly hatched chicks (n = 82) were identified according to their parental treatments. Percentage of inflammation, Heterophil/Lymphocyte (H/L) ratio and antibody titers against sheep red blood cells (SRBC) were evaluated both in adults and their offspring. In adults, compared with controls, stressed groups showed a reduced percentage of inflammation (P < 0.001) and an elevated H/L (P = 0.02), regardless of the challenge. No differences between groups were found in SRBC titers. In offspring, the percentage of inflammation was elevated (P = 0.03) and the SRBC titers were reduced (P = 0.02) in chicks whose parents were stressed, independently of the challenge. The H/L ratio of the chicks did not differ between groups. The immune challenge had no impact on the selected variables either on the adult quails or in their offspring, suggesting that all groups (stressed or not) were capable of dealing with the vaccine challenge. On the other hand, the CHS affected the immune response both in the adults and in their offspring which could have important welfare and productive implications.